The markedness in acquiring do-support in negation and inversion by adult native-Arabic speakers learning English - AL-Makatrah, Elham Salem; Mohamad Subakir Mohd Yasin,; Mohamed Zain Sulaiman,; Al-Khawaldeh, Mohammad (Penerbit Universiti Kebangsaan Malaysia, 2017)
The purpose of this study is to determine whether the markedness phenomenon of Do-support as a specificlanguage property poses greater difficulties for adult Arabic-speaking learners thereby bringing about more L1 transfer than the auxiliary verbs BE and HAVE. Do-support in the inter-language of adult native-Arabic speakers learning English was insufficiently addressed despite the complexity and that Arabic lacks do-support in negation and inversion. This study was conducted to address this gap within the theoretical framework of Differential Markedness Hypothesis (DMH). A sample of 100 Jordanian students attending Mutah University participated in the study where data was collected using a Multiple-Choice Task (MCT), and a Written Production Task (WPT), involving semi-structured interviews with 30 students from the student sample. The study used descriptive and inferential statistics to analyse the data where the findings showed a committed relationship between the auxiliary type and degree of difficulty that learners in both groups experienced with DO, BE and HAVE. Notably, Do-support poses greater difficulty compared to BE and HAVE where its usage is problematic particularly for beginners, resulting in more incidences of the Arabic influence. The data from the interviews support the results of the two tasks: learners find L2 marked features more difficult than L2 features, which are universal and genuinely part of the syntactic structure. The findings in this study will contribute towards a better understanding of how to develop an improved teaching process to more effective on the markedness and difficulty of Do-support compared to BE and HAVE.